EFFECTS OF NEAR-SURFACE CONDUCTANCE ON GLOBAL SATELLITE INDUCTION RESPONSES - Everett M.E.; Constable S.; Constable C.G. (My University, 2003)
A 3-D finite-element simulation of global electromagnetic induction is used to evaluate satellite responses in geomagnetic dipole coordinates for harmonic ring-current excitation of a three-layer mantle overlain by a realistic near-surface conductance distribution. Induced currents are modelled for lithospheric and asthenospheric upper-mantle conductivities in the range σ= 10-4-0.1 S m-1. The magnetic scalar intensity B is calculated at a typical satellite altitude of 300 km. At short periods, T= 2 and 12 h, the induction signal owing to the near-surface conductance is large when a resistive upper mantle is present, but drops off with increasing mantle conductivity. At longer periods, T= 2 d, the near-surface induction signal is generally much smaller and nearly independent of upper-mantle conductivity. The near-surface induction signal is very sensitive to the electrical conductivity of the lithospheric mantle, but only moderately sensitive to that of the asthenospheric mantle. Induced currents are confined to the heterogeneous surface shell at periods of less than 2 h, and flow predominantly in the mantle at periods of longer than 2 d. In the intervening period range, induced currents are partitioned between the near-surface and the upper mantle. These results indicate the importance of carrying out a full 3-D analysis in the interpretation of satellite induction observations in the period range from hours to days.
Keywords: electrical conductivity; electromagnetic induction; geomagnetic variations; sedimentary basins; upper mantle